Burden sharing at the IMF - Mohammed, Aziz Ali (UN New YorkUS, 2003)
Reviews aspects of the financial governance at the IMF. Focuses on how the cost of running the IMF is distributed between its creditors and debtors in the non-concessionary lending operations of the institution through its General Resource Account. Looks also at how concessionary lending by the IMF has been funded.\n \n \n \n \n \n